The impact of participative budgeting on managerial performance and work motivation / Azlin Mastor - Mastor, Azlin (1992)
This research is a study of the participative budgeting practices in Industrial Malaysian Companies . The objectives of this study are : (1) to use data collected by questionnaires and interview sessions to determine whether the participative budgeting is being practiced by Malaysian Industrial Companies located in Klang Valley, and (2) a quantitative analysis to examined the interactive impact of participation managerial performance and work motivation in a budgetary context.